Education – the key indicator of social development of Kerala: An overview on its trend and pattern - Ibrahim Cholakkal
The prime focus on the welfare of the citizens of Kerala has been the hallmark of its development story. Kerala’s achievements in human development are the basis of its national and international fame. Education in Kerala is both inclusive in nature and accessible to all the sections of population. The State, having attained very high rates of literacy and schooling, has a very well developed system that addresses the requirements and demands of all children up to 18 years. This study is descriptive and analytical in nature based on secondary data. The objectives are to examine the trend of literacy, trend of school education, trend of higher secondary and technical education, trend of university and higher education and to analyse the plan outlay and expenditure on education of the 11 th five-year plan. The State, with a few exceptions, has nearly zero dropout rates between classes 1 and 10 among the different sections of population. Education in a sense is the backbone of the Kerala's exceptional development experience. The least square shows that every 10 year will make 8.29 percent improvement in literacy on average. In 1951, the literacy gap was 21.92 and it slow down to 4.04 in 2011. There were 12133 schools in Kerala during 1990-91 and this number has increased to 12981in 2016-17. Out of the total schools, 4695 are under the government sector, 7220 are under private aided sector and the remaining 1066 are under the private unaided sector. In 2001-02, there was only 439 schools in the state they are offering syllabus other than the one prescribed by the state government. These include 331 CBSE schools, 71 ICSE schools, 24 Kendriya vidyalaya and 13 Jawahar Navodayas schools. But in 2016-17 the total number of schools other than state syllabus has increased to 1436. These include 1229 CBSE schools, 157 ICSE schools, 36 Kendriya Vidyalaya and 14 Jawahar Navodays schools. During 2003-04 the drop-out ratio among school students in Kerala was 1.16 percent, and it slow down to 0.21 percent in 2016-17. In higher secondary, university and higher education sectors, there is a hike both in number of institutions and courses in the state. During the 11 th five year plan there is a significant hike in the outlay and in the last year of plan there was Rs.1330.79 crore outlay for education.